Locally graded groups with normal nonmetacyclic subgroups - Kovalenko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We establish the solvability of locally graded groups with normal nonmetacyclic subgroups and prove that the degree of solvability does not exceed 4.